First Identification in Forensic Odontology Endorsed by the American Justice: A Brief Story - Xavier Riaud (Selected Topics in Humanities and Social Sciences Vol. 1, 2021)
Georges Parkman was born in 1790. He studied medicine at Harvard Medical College in 1813. In 1849, Webster killed Parkman. Although the latter’s body was never discovered, his dental prosthesis were located and identified afterwards. Webster was arrested and prosecuted for murder. The investigation of the dental prosthesis by Parkman’s personal dentist positively identified the prostheses, resulting in Webster being condemned to death. This was the first case of forensic dental identification that was approved by a court in the United States.